ACUTE APPENDICITIS COMPLICATING PREGNANCY; EXPERIENCE WITH THE MANAGEMENT OF 50 PATIENTS - Ghazanfar, Abbas; Nasir, Shahid Mahmood; Choudary, Zafar Ali; Ahmad, Waseem (Journal of Ayub Medical College Abbottabad, 2002)
Background: The purpose of this study was to highlight the problems related to acute appendicitis complicating pregnancy and to lay down the principle of their management. Materials and Methods: This study was conducted at Department of Surgery, East Surgical unit Mayo Hospital Lahore from January 1999 to June 2001. It included 50 pregnant patients who presented to emergency department with the diagnosis of acute appendicitis. Results: Of these 50 patients, 16 were primigravida and 34 were multigravida, with the mean age of 26.5 years. Most of these patients were in their second trimester (n= 26), followed by first trimester (n= 19) and third trimester (n= 5). Pain right iliac fossa (72%) was the commonest symptom, followed by vague generalized abdominal pain (18%) and backache (10%). All the patients under went laparotomy; with 86% positive and 14% negative results. There was no maternal mortality in our study, however 14% foetal mortality was noted. Conclusion: Unnecessary delay in diagnosis and management should be avoided as it is directly related to maternal and foetal morbidity and mortality. The general use of this principle may explain the marked improvement in maternal and foetal mortality and morbidity.